Expert Verification of Accounting Information on Financial Instruments for Solving Economic Crimes - Olha Lukova (Облік і фінанси, 2021)
Accounting data on transactions with financial instruments is an important source of information when conducting economic examinations to uncover economic crimes, the share of which is steadily growing every year. The purpose of the article is to determine the methodological components of expert verification of accounting information on financial instruments for solving economic crimes. The study used internal materials of the Kiev Scientific Research Institute of Forensic Expertise. It has been proved that the cause of an offense in the use of financial instruments can be not only selfish motives, but also insufficient professional knowledge of accounting rules, which determines the relevance of expert verification of accounting for such objects. The analysis of the dynamics of requests for expertise was performed. The structure of the circumstances was detected under which the expertise of issues related to the accounting of transactions of agricultural enterprises with financial instruments was initiated. The subject structure of the conducted examinations was revealed. The sources of obtaining information used for the examination of accounting of transactions of agricultural enterprises with financial instruments have been identified. The procedures for the examination of accounting of transactions of agricultural enterprises with financial instruments have been systematized. Typical deviations have been determined that can be identified as a result of the examination of accounting for transactions of agricultural enterprises with financial instruments. The implementation of the methodological components of the expert verification of accounting information on financial instruments indicated by the author ensures the formation of more substantiated conclusions about the legality of transactions with financial instruments, and respectively, it contributes to the disclosure of economic crimes.